Q. 104.1( 29 Votes )

If one of the zer

Answer :

let p(x) = x2 + ax + b

And let α be one of the zeroes

- α is the other zero of the polynomial p(x)

Product of the zeroes = constant term ÷ coefficient of x2

Product of the zeroes = b

α(- α) = b

- α2 = b

i.e. b is negative.

Sum of the zeroes = - (coefficient of x) ÷ coefficient of x2

α - α = - a

0 = - a

a = 0

The polynomials can be written as x2 - α2 (No linear term and negative constant term)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses